Language Politeness in Indonesian Language Instruction at SDN Satu Seruni Mumbul - Rini Kurniatun Sari; Dedi Purnama, Lalu; Usman, Usman; Jaelani Al Pansori, Muh. (Jurnal Multidisiplin Sahombu, 2026)
This study examines the forms of linguistic politeness and the factors influencing its use in Indonesian language instruction at SDN Satu Seruni Mumbul. Employing a descriptive qualitative design, the study involved teachers and students as participants, with spoken classroom interactions serving as the unit of analysis. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The findings demonstrate that linguistic politeness is realized through mitigated directives, expressive utterances such as appreciation and apologies, the appropriate use of address terms and pronouns, and persuasive strategies that reduce coercive communication. Furthermore, linguistic politeness is influenced by four interrelated factors: teacher modeling, family communication practices, exposure to digital media, and the broader school social environment. The study concludes that Indonesian language instruction functions not only to develop students’ linguistic competence but also to reinforce communicative ethics and character development. These findings underscore the pivotal role of teachers in cultivating a culture of linguistic politeness through instructional design and exemplary communicative practices.